(untitled) (Revista Argentina de Cirugía, 2022)
Background: Ambulatory Surgery (CMA) includes those surgical procedures with general or regional anesthesia and postoperative required where the patient returns to his home the same day of surgery. It is a condition that the patient does not spend the night at the institution. With the development of less invasive techniques and improved anesthetic drugs outpatient procedures are becoming more frequent. Objective: To analyze the results of patients operated on an outpatient basis over time. Setting: Ambulatory Surgery Unit, Hospital Italiano de Buenos Aires. Population: 82.901 patients operated between November 1993 and December 2009. Method: Analysis of a prospective database, stratification by service, complexity, type of anesthesia, outpatient/inter- nal relationship, grounds for suspension, conversion, complications and costs. Results: 82.901 surgeries were performed, representing 29.5% of hospital procedures, 70.24% were CMA, 8.2% discontinuation rate, conversion rate 0.89%, 0.002% died, the cost/time in the operating room was 10% UCA cheaper, saving 58.227 days/bed.